Teaching and Social Justice: Integrating Multicultural and Feminist Theories in the Classroom.
DOI: 10.1037/10929-006
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural and Feminist Literatures: Themes, Dimensions, and Variations.

Abstract: In this brief chapter, we summarize the parallel and divergent features of the multicultural and feminist theoretical positions discussed in chapters 2 through 5. It is our hope that this overview, along with the common principles, foundations, and converging themes discussed in chapter 1, will provide the foundation necessary for educators to articulate meaningful pedagogical models. Common to all the multicultural and feminist models discussed in previous chapters is the goal of reenvisioning pedagogy such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…The ISJ pedagogy model (Sinacore & Enns, 2005) is a frame work for teaching and training in professional psychology that centers on critical concepts such as development, collaboration, feminism, and multiculturalism (Bedi et al, 2011). In reviewing feminist and multicultural approaches to education, Sinacore and Enns suggested that these approaches focus on the following dimensions to varying degrees: individual empowerment and so cial change, knowledge and the knower, oppression and privilege, and reflexivity and self-awareness.…”
Section: Isj Pedagogy Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The ISJ pedagogy model (Sinacore & Enns, 2005) is a frame work for teaching and training in professional psychology that centers on critical concepts such as development, collaboration, feminism, and multiculturalism (Bedi et al, 2011). In reviewing feminist and multicultural approaches to education, Sinacore and Enns suggested that these approaches focus on the following dimensions to varying degrees: individual empowerment and so cial change, knowledge and the knower, oppression and privilege, and reflexivity and self-awareness.…”
Section: Isj Pedagogy Modelmentioning
confidence: 99%
“…The goal of this dimension is to help students understand indi vidual and social structures in order to transform traditional sys tems that are considered oppressive (Sinacore & Enns, 2005). To facilitate this transformation, instructors must provide students with the tools necessary to achieve individual change, as well as encourage them to become involved in larger social change.…”
Section: Individual Empowerment and Social Changementioning
confidence: 99%
See 3 more Smart Citations